2019
DOI: 10.1101/717561
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Termite mounds contain distinct methanotroph communities that are kinetically adapted to elevated methane concentrations

Abstract: 20Termite mounds have recently been confirmed to mitigate approximately half of termite 21 methane (CH4) emissions, but the aerobic methane-oxidizing bacteria (methanotrophs) 22 responsible for this consumption have not been resolved. Here we describe the 23 abundance, composition, and kinetics of the methanotroph communities in the mounds 24 of three distinct termite species. We show that methanotrophs are rare members of the 25 termite mound biosphere and have a comparable abundance, but distinct composition… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Methanotrophic bacteria are responsible for the CH 4 uptake in aerobic soils, and their possible presence in termite mounds was already suggested by Seiler et al (1984). Other studies have confirmed their presence (Chiri et al, 2019;Ho et al, 2013), and recent studies have been focusing on whether https://doi.org/10.5194/bg-2020-384 Preprint. Discussion started: 16 November 2020 c Author(s) 2020.…”
Section: Ch 4 and Co 2 Emissionsmentioning
confidence: 98%
See 1 more Smart Citation
“…Methanotrophic bacteria are responsible for the CH 4 uptake in aerobic soils, and their possible presence in termite mounds was already suggested by Seiler et al (1984). Other studies have confirmed their presence (Chiri et al, 2019;Ho et al, 2013), and recent studies have been focusing on whether https://doi.org/10.5194/bg-2020-384 Preprint. Discussion started: 16 November 2020 c Author(s) 2020.…”
Section: Ch 4 and Co 2 Emissionsmentioning
confidence: 98%
“…Other estimates range widely between no observable uptake to very strong uptake rates (up to 80%) (Khalil et al, 1990;Macdonald et al, 1998;Nauer et al, 2018;Sugimoto et al, 1998a). A more elaborate overview of recent findings on termite mound CH 4 uptake processes can be found in Nauer et al (2018) and Chiri et al (2019). The role of possible mound CH 4 uptake should also be acknowledged for the measurement of individual termite emissions (Table 2, upper part): most literature values, including values from this study, are based on termite incubation in presence of mound material, with ongoing CH 4 uptake, wherefore actual termite CH 4 emission values might be higher.…”
Section: Ch 4 and Co 2 Emissionsmentioning
confidence: 99%
“…The V4 hypervariable region of the 16S rRNA gene was ampli ed using the universal Earth Microbiome Project primer pairs 515FB 5′-GTGYCAGCMGCCGCGGTAA-3′ and 806RB 5′-GGACTACNVGGGTWTCTAAT-3′ 57 , as per previously described cycling conditions 58 . The employed reaction conditions and thermal pro les of the qPCR assays have been previously described 36 . Ampli cation from different dilutions (from undiluted to 1:100 dilution in PCR-grade water) of DNA extracts was tested, and the dilution resulting in the highest yield and quality of PCR product was used for the qPCR assays.…”
Section: Quantitative Pcrmentioning
confidence: 99%
“…Note that this analysis cannot detect uncultured MOB with unknown 16S rRNA gene sequences. Data processing of the pmoA gene amplicon sequences followed our previously published pipeline 36,61 , with minor modi cations. All processing steps were performed in the QIIME 2 platform and, instead of assigning the raw sequences to operational taxonomic units, raw sequences were denoised using the DADA2 pipeline 62 , yielding 280 high-quality pmoA amplicon sequence variants (pmoA-ASVs).…”
Section: Amplicon Sequencingmentioning
confidence: 99%
See 1 more Smart Citation